Jatibaru Raya Road Closure: Jakarta Governor's Incremental Policy in Managing the Tanah Abang Market Area - Angga Sukmara Christian Permadi; Sri Budi Eko Wardani (Social and Political Science Faculty - Universitas Tidar, 2018)
The policy of closing Jatibaru Raya Road on December 22, 2017, has caused new problems because the road closure has caused public losses. The public policy applied by Governor Anies indicated that he had a strong political contract with the community and one of the powerful figures in Tanah Abang so that the policy benefited the people of Tanah Abang who had been disciplined during the previous governor's term. These issues are very relevant to be studied using qualitative methods with a grounded approach to obtain material and in-depth information. Regarding the road closure policy, the existing policy is seen as a step in the realization of Anies campaign promises to establish 200,000 MSMEs at the time of the DKI Jakarta Pilkada in 2017. The public policy for road closure is basically an incremental policy because there are not many policy programs that have been running and was designed during the previous governor's term. The implementation of this policy has made Governor Anies considered maladministration by the Ombudsman, thus giving rise to recommendations for the position of Anies as governor. Keywords: Public Policy; Inkremental; Maladministration.